(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
In this study, has been discussed the issue of non-interest income and its impact on the Iraqi banking sector profit for the period between (2008-2017) as it was the main objective of the study is to find the relationship between the non-interest income and the profits of the banking sector in order to know the size of the sector’s dependence on non-interest income As well as an analysis of its profitability compared to selected countries, And to test hypotheses, the financial ratios and some statistical tests to determine the stability of the time series such as the test (Correlegram , Dickey -Fuller (depending on the statistical program (E-Views V8) and a simple linear regression method by (Minitab v14), the study has been found that there is a statistically significant relationship between non-interest income and total profits of the banking sector , Non-interest income in the banking sector has increased compared to the US, China, Canada, Malaysia and Germany, The study recommended the need to activate the other side which is interest income as it represents the basic function of banks through the effective and rational use of liquidity in granting credit to support economic development in the country.